2009
DOI: 10.1002/maco.200805177
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and corrosion behavior of thermophilic (55 °C) SRB Desulfotomaculum kuznetsovii isolated from cooling tower in petroleum refinery

Abstract: Desulfotomaculum kuznetsovii (D. kuznetsovii), a thermophilic sulfate-reducing bacterium (SRB), was identified in a cooling tower of a petroleum refinery by 16S rRNA gene sequencing and its functional gene encoding dissimilatory sulfite reductase (dsrAB). The thermophilic sulfate-reducing bacterial species have been reported for the first time in the cooling towers of an Indian petroleum refinery. The protein coded by dsrAB gene was cloned, expressed, and identified using recombinant DNA technology. Weight los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Instead, after 28 d, members of the family Peptococcaceae (a family within the Firmicutes), including Desulfotomaculum spp., were dominant, with acetate oxidation coupled with Fe(III) and sulfate reduction ( Fig 5A, 5C and 5E ). Several species in the genus Desulfotomaculum are known to reduce sulfate, coupled with oxidation of acetate to CO 2 via an acetyl-CoA pathway [ 45 49 ]. The observed consumption of ~5 mM acetate and ~4 mM sulfate was in good agreement with the stoichiometry for sulfate reduction coupled with acetate oxidation (CH 3 COO − + SO 4 2− → 2HCO 3 − + HS − ), sulfide and bicarbonate being likely products, but not directly observed.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, after 28 d, members of the family Peptococcaceae (a family within the Firmicutes), including Desulfotomaculum spp., were dominant, with acetate oxidation coupled with Fe(III) and sulfate reduction ( Fig 5A, 5C and 5E ). Several species in the genus Desulfotomaculum are known to reduce sulfate, coupled with oxidation of acetate to CO 2 via an acetyl-CoA pathway [ 45 49 ]. The observed consumption of ~5 mM acetate and ~4 mM sulfate was in good agreement with the stoichiometry for sulfate reduction coupled with acetate oxidation (CH 3 COO − + SO 4 2− → 2HCO 3 − + HS − ), sulfide and bicarbonate being likely products, but not directly observed.…”
Section: Resultsmentioning
confidence: 99%
“…It plays an important role in MIC ( Cetin et al, 2007 ) by accelerating cathodic depolarization and decelerating anodic depolarization ( Cetin and Aksu, 2009 ). The ability of members of this genus to corrode steel has been studied extensively in laboratory experiments: D. nigrificans ( Mystkowska et al, 2015 ), D. orientis ( Ren and Wood, 2004 ), and D. kuznetsovii ( Anandkumar et al, 2015 ). Members of this genus are usually associated with oil, and have been isolated from the crude oil field, oil production wells, or even the cooling towers of a petroleum refinery ( Cetin et al, 2007 ; Cetin and Aksu, 2009 ; Anandkumar et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that the biofilm formation initiates after lapse of a certain incubation period and that the corrosion products (iron sulfides) start affecting the biofilm after a certain incubation period. Anandkumar et al [18]; Anandkumar and Rajeshkar, [19], investigated the role of Desulfotomaculum geothermicum and Desulfotomaculum kuznetsovii in mild steel corrosion. The presence of bacteria enhances corrosion by accelerating cathodic reaction and suppressing anodic reaction.…”
Section: Introductionmentioning
confidence: 99%